PANDANGAN ALBERT BANDURA TENTANG TEORI KOGNITIF SOSIAL DAN KONTEKSTUALISASINYA DALAM SISTEM PENDIDIKAN HINDU - Gede Agus Siswadi (Jurnal Pendidikan Agama, 2022)
Good character is an essence that is expected to be formed from education. However, the quality seems still far from expected. The teacher's role is very important in instilling moral values, character, and a good personality. So that an effort is needed to rethink a method, theory, strategy, and the right approach to instil a good character in students. Social cognitive theory from Albert Bandura emphasizes aspects of students' social environment that have a major influence on students. Students need a model that can be imitated in behaviour. This research uses the library research method. The results in this study are 1). In Bandura's view, an educator or teacher is to act as a model that students can imitate. 2). The student's character is processed through imitation, namely a student trying to change himself through what is observed in the social environment. 3). According to Bandura, student character is formed through four processes, namely attentional, retentional, behavioral production, and motivational processes. 4). In the Hindu religious education system, Bandura's social cognitive theory is relevant to the formation of good morals and character. In this case, the religious teacher must be a role model for students, according to the religious teachings given.